2018
DOI: 10.1152/japplphysiol.01006.2017
|View full text |Cite
|
Sign up to set email alerts
|

Beetroot juice ingestion during prolonged moderate-intensity exercise attenuates progressive rise in O2 uptake

Abstract: Nitrate-rich beetroot juice (BR) supplementation has been shown to increase biomarkers of nitric oxide availability with implications for the physiological responses to exercise. We hypothesized that BR supplementation before and during prolonged moderate-intensity exercise would maintain an elevated plasma nitrite concentration ([[Formula: see text]]), attenuate the expected progressive increase in V̇o over time, and improve performance in a subsequent time trial (TT). In a double-blind, randomized, crossover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 59 publications
3
33
5
Order By: Relevance
“…Issues for future study • Individual responsiveness to nitrate supplementation in distance running, including the effect of athletes' caliber as it seems less effective in elite athletes (Jonvik et al, 2015) • Effect of protocols involving intake during distance events to maintain elevated plasma nitrite concentrations (Tan et al, 2018) • Interaction with other supplements-CHO, caffeine, etc.…”
Section: Commentary 1: Dietary Practices Of East African Runnersmentioning
confidence: 99%
“…Issues for future study • Individual responsiveness to nitrate supplementation in distance running, including the effect of athletes' caliber as it seems less effective in elite athletes (Jonvik et al, 2015) • Effect of protocols involving intake during distance events to maintain elevated plasma nitrite concentrations (Tan et al, 2018) • Interaction with other supplements-CHO, caffeine, etc.…”
Section: Commentary 1: Dietary Practices Of East African Runnersmentioning
confidence: 99%
“…In this study, VO 2 steady-state of moderate exercise intensity was reduced significantly after ingestion of 16.8 mmol of NO 3 − , tended to be lower after intake of 8.4 mmol NO 3 − , and was unaffected by 4.2 mmol of NO 3 − [ 37 ]. Higher doses of BJ supplementation (2 × 70 mL doses per day, ~ 6.2 mmol of NO 3 − per 70 mL) before and during prolonged moderate-intensity exercise might be necessary to attenuate the progressive rise in VO 2 and reduce muscle glycogen depletion [ 52 ], improving mechanical efficiency during a prolonged constant-load test at VT1 intensity. Further, IOC consensus statement concludes that longer periods (> 3 days) of NO 3 − supplementation could increase sport performance in highly-trained athletes [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, ingestion of BRJ was found to significantly decrease VO 2 , regardless of the duration of BRJ consumption and type of intervention Kelly et al 2014;Kuennen et al 2015;Lansley, Winyard, Fulford, et al 2011;Masschelein et al 2012;Muggeridge et al 2013Muggeridge et al , 2014Rienks et al 2015;Tan et al 2018;Thompson et al 2017;Vanhatalo et al 2010;Whitfield et al 2016;Wylie, Kelly, Fulford, et al 2013). Tan et al (2018) found that a 3day supplementation of BRJ before, and ingestion of BRJ during moderate-intensity exercise attenuated the increase in VO 2 that normally accompanies sportive performance, compared to placebo (Tan et al 2018). Additionally, this study reports that BRJ reduced the amount of glycogen depletion during exercise by 16% as compared to the placebo, which indicates that the metabolic demand of the muscle is decreased.…”
Section: General Effects Of Brj On Skeletal Muscles and Oxygen Consummentioning
confidence: 98%
“…Additionally, this study reports that BRJ reduced the amount of glycogen depletion during exercise by 16% as compared to the placebo, which indicates that the metabolic demand of the muscle is decreased. Both the lower VO 2 and the reduced glycogen depletion could be caused by either an improvement in mitochondrial efficiency or in contractile efficiency of skeletal muscle (Tan et al 2018). However, there is no consensus on the precise mechanism.…”
Section: General Effects Of Brj On Skeletal Muscles and Oxygen Consummentioning
confidence: 99%
See 1 more Smart Citation